Trends and drivers of agricultural productivity in Nigeria - Oni, Omobowale Ayoola; Nkonya, Ephraim M.; Pender, John L.; Phillip, Dayo; Kato, Edward (International Food Policy Research Institute, 2009)
Agriculture is the economic mainstay of the majority of households in Nigeria (Udoh, 2000) and is a significant sector in Nigeria’s economy (Amaza, 2000). The important benefits of the agricultural sector to Nigeria’s economy include: the provision of food, contribution to the gross domestic product (GDP), provision of employment, provision of raw materials for agro-allied industries, and generation of foreign earnings labor(until the early 1970s; agricultural exports were the main source of foreign exchange earnings). A sectoral analysis in 2006 of the real GDP indicated that the agricultural sector contributed to about 42 percent of the GDP compared with 41.2 percent in 2005 (CBN, 2006). The growth rate of the contribution of the agricultural sector to the GDP at 1990 constant basic prices grew from 4.2 percent in 2002 to 7.2 percent in 2006. The agricultural sector also employed over 60 percent of the total labor force in Nigeria in 1999 (Adeoti, 2002). The advent of oil in the early 1970s made Nigeria highly dependent on oil revenue, with the performance of the agricultural sector adversely affected over years. Though the growth rate in the agricultural sector in Nigeria increased from an average of about 3 percent in the 1990s to about 7 percent in mid 2000, the food security/sufficiency status of Nigerians continued to decline. (Adeoti 2002) The dismal performance of the agricultural sector in terms of its contribution to Nigeria’s yearly total revenue in the last three decades prompted the government to initiate several agricultural schemes and programs to enhance agricultural productivity in Nigeria, which include the following: the River Basin Development Authorities, the National Accelerated Food Production Project, the Agricultural Development Project, Operation Feed the Nation, the Green Revolution, the National Directorate of Food, Roads and Rural Infrastructure, the Agricultural Credit Guarantee Scheme Fund, the National Special Programme for Food Security, Root and Tuber Expansion Project, and the National Fadama I and II program. Similarly, a series of studies have been carried out to assess agricultural productivity and its drivers in Nigeria, which include: Adebayo (2006), Adeoti (2002), Ajani (2002), Ajibefun et al. (1996), Ajibefun and Abdulkadri (1999), Ajibefun and Daramola (2003), Amaza (2000), Awotide (2004), Ogundele (2003), Ogundele and Okoruwa (2006), Okike (2000), Oredipe (1998), Rahji (2003), and Udoh (2000). None of the aforementioned studies, however, has assessed productivity within the context of agro-ecological zones. This paper intends to examine productivity trends and patterns in Nigeria as well as the drivers of such trends in the last several years, specifically during 1995-2006.